(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
Scholars and practitioners of international relations have devotedincreasing attention to how ceasefires, once achieved, may be translated intosustained peace. In recent years, the United Nations, the World Bank, and theUnited States and other governments have revamped their institutionalarchitecture for addressing post-conflict reconstruction and peace building.The creation in 2006 of a UN Peace- building Commission exemplifies thesechanges. The relationship between weak states and the durability of peace hasacquired new emphasis in IR research. This article analyzes recent conceptualdevelopments in post-conflict peace building, relating them to new thinkingabout fragile states. It then analyzes the international architecture foraddressing post-conflict peace building, identifying gaps, and analyzing likelypolicy challenges in the near future. We argue that despite important analyticinsights and institutional changes, serious challenges persist in efforts toprevent wars from recurring.